Injectable interferon beta-1b for the treatment of relapsing forms of multiple sclerosis - Slobodan M Jankovic (Dove Medical Press, 2010)
Slobodan M JankovicPharmacology Department, Medical Faculty, University of Kragujevac, Kragujevac, SerbiaAbstract: Multiple sclerosis (MS) is chronic inflammatory and demyelinating disease with either a progressive (10%–15%) or relapsing-remitting (85%–90%) course. The pathological hallmarks of MS are lesions of both white and grey matter in the central nervous system. The onset of the disease is usually around 30 years of age. The patients experience an acute focal neurologic dysfunction which is not characteristic, followed by partial or complete recovery. Acute episodes of neurologic dysfunction with diverse signs and symptoms will then recur throughout the life of a patient, with periods of partial or complete remission and clinical stability in between. Currently, there are several therapeutic options for MS with disease-modifying properties. Immunomodulatory therapy with interferon beta-1b (IFN-β1b) or -1a, glatiramer and natalizumab shows similar efficacy; in a resistant or intolerant patient, the most recently approved therapeutic option is mitoxantrone. IFN-β1b in patients with MS binds to specific receptors on surface of immune cells, changing the expression of several genes and leading to a decrease in quantity of cell-associated adhesion molecules, inhibition of major histocompatibility complex class II expression and reduction in inflammatory cells migration into the central nervous system. After 2 years of treatment, IFN-β1b reduces the risk of development of clinically defined MS from 45% (with placebo) to 28% (with IFN-β1b). It also reduces relapses for 34% (1.31 exacerbations annually with placebo and 0.9 with higher dose of IFN-β1b) and makes 31% more patients relapse-free. In secondary-progressive disease annual rate of progression is 3% lower with IFN-β1b. In recommended doses IFN-β1b causes the following frequent adverse effects: injection site reactions (redness, discoloration, inflammation, pain, necrosis and non-specific reactions), insomnia, influenza-like syndrome, asthenia, headache, myalgia, hypoesthesia, nausea, paresthesia, myasthenia, chills and depression. Efficacy of IFN-β1b in relapsing-remitting MS is higher than that of IFN-β1a, and similar to the efficacy of glatiramer acetate. These facts promote IFN-β1b as one of the most important drugs in the spectrum of immunological therapies for this debilitating disease.Keywords: multiple sclerosis, interferon beta 1b, mechanism of action, efficacy, safety